EMPLOYEE PAYMENT COMPUTERIZATION SYSTEM AT PT REJEKI JAYA ABADI - Dina Siska Rahmawati; Agustinus Budi Santoso (Lembaga Pengembangan Kinerja Dosen, 2021)
In line with the development of science and computer technology and facing the current era of information technology, it is necessary to prepare human resources who have high quality, expertise, and competitiveness in facing competition in the field of work. In the information era, technology is increasingly sophisticated so that giving or receiving information will be faster. One of the tools that can support information technology is a computer. The computer is a tool for the achievement of a computerized system design, the existence of a computer is needed to strengthen its existence in helping routine human activities. At PT Rejeki Jaya Abadi Semarang where the author conducted a survey, he had difficulties because he still used the manual method of payroll. The problems or obstacles faced by PT Rejeki Jaya Abadi Semarang are the more employees, the more difficult it is to calculate employee salaries because manual calculations will take a long time. For this reason, in this final project the author tries to provide a new system, which is expected to reduce existing deficiencies by changing some of the old systems into modern systems so that the payroll process can be carried out as efficiently as possible. The development of this new system does not change the development of existing procedures but displays it in a new format in the system, namely Microsoft Visual Basic (Vb).